Hazard Identification Risk Assessment and Determining Control (HIRADC) Method for Shoe Cutting Dies Production - Sjarifudin, Didin; Kurnia, Hibarkah; Nuryono, Arif; Tambunan, Erwin Barita Maniur (Jurnal Sistem Teknik Industri, 2023)
Along with high orders from customers for shoe products in apparel companies, the production department must also support productivity results. The production process has experienced several problems, including the number of work accidents and potential levels of work accidents, and the absence of safe work accident control measures in the cutting die area for the shoe production process. The purpose of this study is to analyze the types of work accidents and provide recommendations for controlling sources of hazard to reduce or eliminate the level of risk involved in the shoe molding process. The method used in this study uses the Hazard Identification Risk Assessment and Determining Control (HIRADC) method combined with the Focus Group Discussion (FGD) method. The findings of this study have obtained data before repair with 16 hazard potentials consisting of 6 medium hazard potentials and 10 low hazard potentials. Improvements that have been made in accident risk control for each potential hazard include technical controls, administrative controls, and document controls. The results of this study resulted in a reduction in the risk of work accidents after repairs to 16 low hazard potentials and no moderate hazard potentials. So from these results, it can be concluded that the decrease in risk level from medium risk to low risk proves the success of corrective actions.